Wyobrażenia zbiorowe – próba kategoryzacji pojęcia (W kręgu wyobrażeń zbiorowych. Polityka, władza, społeczeństwo, 2019)
The aim of the text is to define and examine the concept of collective representations which was introduced by Émile Durkheim many years ago, but since that not many scholars have brightly analysed it. According to the author, collective representations can be described as the system of following elements: myths and stereotypes, collective memory, collective identity, axio-normative system (including culture and religion) and collective emotions. All the elements mentioned above are related to each other, so one can say that the system constantly works. That is why collective representations are not constant, they regularly evolve according to political atmosphere and ideological context.